2021
DOI: 10.1155/2021/5527060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture on Sleep via the Dopamine System of the HPA Axis in Rats after Cage Change

Abstract: Background. Insomnia is often related to stressful events. The hypothalamus-pituitary-adrenal (HPA) axis is related to stress, and dopamine (DA) and DA receptors are involved in the regulation of HPA axis. Electroacupuncture (EA) can improve sleep in individuals with insomnia, but the mechanism is unclear. We demonstrated that EA can improve sleep in rats after cage change through DA and the DA receptors in the HPA axis. Methods. A rat model of insomnia was established by cage change to a dirty cage. The rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The hypothalamic levels of DA, corticotropin-releasing hormone, adrenocorticotropic hormone (ACTH), and cortisol (CORT) increased in the EA group treated at the BL18 and ST36 acupoints. Moreover, EA treatment increased D1R and D2R mRNA levels ( Xie et al, 2021 ). The DU20, HT7, and SP6 acupoints were used for EA treatment in a rat model of insomnia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothalamic levels of DA, corticotropin-releasing hormone, adrenocorticotropic hormone (ACTH), and cortisol (CORT) increased in the EA group treated at the BL18 and ST36 acupoints. Moreover, EA treatment increased D1R and D2R mRNA levels ( Xie et al, 2021 ). The DU20, HT7, and SP6 acupoints were used for EA treatment in a rat model of insomnia.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture therapy, which has beneficial effects on neuroprotection, has been shown to improve serum and hippocampal 5-HT and DA levels in depression model rats ( Li et al, 2021 ). Interestingly, several studies have shown increased levels of 5-HT expression in different sites, such as the serum ( Yu et al, 2022 ), hypothalamus ( Bo et al, 2017 ; Xie et al, 2021 ), and hippocampus ( Bo et al, 2017 ; Cao et al, 2022 ) following acupuncture treatment. Among these studies, one showed an improvement in both 5-HT and DA expression levels ( Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroacupuncture can significantly increase DA and lower TNF-α levels, so as to alleviate the immunosuppressive response and inflammatory damage of intestinal tissues and organs (Li et al, 2021). In cage-changed rats, electroacupuncture is capable of improving sleep quality by increasing the levels of DA and DA receptors in the hypothalamic-pituitary-adrenal (HPA) axis (Xie et al, 2021). 9.2 Amino acid neurotransmitters 9.2.1 γ-Aminobutyric acid GABA is a distinct neurotransmitter of the ascending inhibitory system, which is widely distributed in the CNS.…”
Section: Dopaminementioning
confidence: 99%